Kebebasan Beragama dan Demokratisasi di Indonesia - M. Zainuddin (el Harakah: Jurnal Budaya Islam, 2009)
The objective of this research is to understand the religious freedom and the process of democratization in Indonesia. The result of this research shows that the religious freedom in Indonesia is regulated by the law. In this sense, religious freedom means freedom to choose and believe in certain religion, it does not mean that people have freedom to be atheism. In fact, the religious freedom in Indonesia has not run well since there is a religion banned by claiming it as a wrong and deviate religion. Furthermore, the violence by a religion to another religion is common in social life. Tujuan penelitian ini untuk memahami kebebasan beragama dan proses demokratisasi di Indonesia. Hasil penelitian ini menunjukkan bahwa kebebasan beragama di Indonesia diatur oleh undang-undang. Dalam pengertian ini, kebebasan beragama berarti kebebasan memilih dan percaya pada agama tertentu, tidak berarti orang memiliki kebebasan untuk bersikap ateis. Sebenarnya, kebebasan beragama di Indonesia belum berjalan dengan baik karena ada agama yang dilarang dengan mengklaimnya sebagai agama yang salah dan menyimpang. Selanjutnya, kekerasan oleh agama ke agama lain biasa terjadi dalam kehidupan sosial.